First description of the male Megalogomphus flavicolor (Fraser, 1923) from the fringe of Raimona National Park, Assam, India (Odonata: Gomphidae) - Payra, Arajush; Philip, Joel George; Islam, Nazrul; Mardi, Saurabh; Barman, Rathin; Deka, Sanatan; Koparde, Pankaj (Zootaxa, 2026)
Megalogomphus flavicolor (Fraser, 1923) was described based on a female specimen from Bihar. To date, no formal description has been available for the male. The present communication deals with the first description of the previously unknown male of M. flavicolor, along with the supplementary notes on the morphology of female, based on a male and a female specimen collected from the fringe area of Raimona National Park in Assam, Northeast India. The present record also designates the first record of M. flavicolor for the northeast Indian state Assam, representing easternmost distributional range of the species.